Three new species of Pancorius Simon, 1902 (Araneae: Salticidae) from China - Zhou, Yuchen; Wang, Shulin; Peng, Xianjin (Zootaxa, 2026)
Three new species of Pancorius Simon, 1902 are described from China and named as P. subyingjiang sp. nov. (female), P. yangming sp. nov. (male, female) and P. yunnan sp. nov. (female). Detailed descriptions, photos of somatic features and copulatory organs, as well as a distribution map are provided. Nucleotide data for the barcoding gene, cytochrome c oxidase subunit I (COI) of P. yangming sp. nov. (male, female) are provided.